Muslim women's views and experiences of family planning in Saudi Arabia: a qualitative study - Noura Alomair; Samah Alageel; Nathan Davies; Julia V. Bailey (BMC, 2023)
Abstract Background Islamic beliefs are associated with decreased contraceptive use compared to other religions, and Muslim women's contraceptive needs are often unmet. Research is needed to provide an in-depth understanding of the complex set of barriers to Muslim women's contraceptive use. Therefore, we aimed to explore Muslim women's awareness and experiences with family planning in Saudi Arabia and investigate barriers to contraceptive use and access to family planning. Methods A qualitative study using semi-structured interviews with women in a public hospital, in Riyadh, Saudi Arabia, between January and June 2019. Data was analysed using reflexive thematic analysis. Results Twenty-eight women participated in the study. Women's contraceptive awareness was limited to two methods. Women expressed positive attitudes towards family planning and did not believe it is forbidden in Islam. Barriers to contraception use included lack of knowledge, misconceptions, fear of side effects, family and community and social norms. Many women expressed that they have the right to use contraception, even if their husbands disapprove. Our findings show that healthcare providers rarely offered contraceptive advice, even when requested. Healthcare providers often prescribe oral contraceptives without offering information on other methods available. Conclusion Our findings suggest that education plays a fundamental role in reproductive autonomy. Men's role in family planning should be encouraged through sharing reproductive responsibility and supporting women's contraceptive choices. Efforts should be directed towards improving women's awareness of different methods of contraception.